Effects of crown condition, tree damage, and site Quality on forest health in Gapoktan Wana Karya I - Dhiyaulhaq Al Mugni; Rahmat Safe'i; Eny Puspasari; Hari Kaskoyo (Universitas Lambung Mangkurat, 2024)
Forests are land in which there are flora and fauna life that are symbiotic with each other so as to form various ecosystems. Forests have a very important role for the components that make up them and for the surrounding environment. Damage that occurs to trees and their constituent soil can disrupt the ecosystem in them which can have an impact on the function of the forest. The importance of the role of forests for the surrounding environment, it is necessary to monitor the health condition of forests to have benefits so that forests are monitored for sustainability so that forests can carry out their functions optimally. This study aims to find the value of forest health conditions in land cultivated by Gapoktan Wana Karya I (Gapoktan WK) and to determine the influence of tree damage indicators, header conditions, and site quality on forest health. The forest health condition in this study was monitored through three indicators, namely tree damage, header condition, and site quality with Forest Health Monitoring (FHM) as the method. Then for the influence use simple linear regression. The results of the research on forest health conditions in Gapoktan WK showed an average value of 4.5, which was included in the medium category. The results of the simple linear regression analysis showed that the indicators of canopy condition and site quality had a unidirectional influence on forest health while the tree damage indicators had an influence but in the opposite direction on the forest health value.